Complementarity determining regions in SARS-CoV-2 hybrid immunity - Frans, Glynis; Dillaerts, Doreen; Dehaemers, Tom; Van Elslande, Jan; De Leeuw, Jonas; Boon, Lise; Maes, Wim; Callewaert, Nico; Calcoen, Bas; Ancheva, Lina; Cockx, Maaike; Geukens, Nick; et al. (Frontiers in Immunology, 2023)
Pre-vaccination SARS-CoV-2 infection can boost protection elicited by COVID-19 vaccination and post-vaccination breakthrough SARS-CoV-2 infection can boost existing immunity conferred by COVID-19 vaccination. Such ‘hybrid immunity’ is effective against SARS-CoV-2 variants. In order to understand ‘hybrid immunity’ at the molecular level we studied the complementarity determining regions (CDR) of anti-RBD (receptor binding domain) antibodies isolated from individuals with ‘hybrid immunity’ as well as from ‘naive’ (not SARS-CoV-2 infected) vaccinated individuals. CDR analysis was done by liquid chromatography/mass spectrometry-mass spectrometry. Principal component analysis and partial least square differential analysis showed that COVID-19 vaccinated people share CDR profiles and that pre-vaccination SARS-CoV-2 infection or breakthrough infection further shape the CDR profile, with a CDR profile in hybrid immunity that clustered away from the CDR profile in vaccinated people without infection. Thus, our results show a CDR profile in hybrid immunity that is distinct from the vaccination-induced CDR profile.